Beginning JavaFX Platform - PremKumar, Lawrence (Apress, 2012)
This book covers all the essential features of JavaFX Platform and will teach you various aspects of the language and UI elements. It has been designed to proceed from less complex to more complex topics in a gradual manner so that you are not overwhelmed with myriad of concepts to learn and understand upfront. This book is for Flash, Silverlight, and other RIA developers looking to use and integrate JavaFX in their RIA, whether it is for desktop or mobile environments. However, our goal is to teach you JavaFX from the ground up, and you don't need prior programming expertise to use this book and hence this book is also suitable for those who are new to RIA development. Your time as a reader is extremely valuable, and you are likely waiting to read a pile of books besides this one. So we have made it concise by tightening things up and eliminating redundant examples. We recommend that you be hands-on while reading this book, as it is mostly code-driven and will help you learn the concepts through practical exploration while reading. This way, you can actually get to program with JavaFX, rather than just reading the book, and you can also become comfortable and productive with it readily.